Insulin rapidly upregulates protein kinase Cδ gene expression in skeletal muscle - Horovitz-Fried, Miriam; Cooper, Denise R.; Patel, Niketa A.; Cipok, Michal; Brand, Chagit; Bak, Asia; Inbar, Aya; Jacob, Avraham I.; Sampson, Sanford R. (Cellular signalling, 2006)
Recent studies in our laboratories have shown that Protein Kinase C delta (PKCδ) is essential for insulin-induced glucose transport in skeletal muscle, and that insulin rapidly stimulates PKCδ activity skeletal muscle. The purpose of this study was to examine mechanisms of regulation of PKCδ protein availability. Studies were done on several models of mammalian skeletal muscle and utilized whole cell lysates of differentiated myotubes. PKCδ protein levels were determined by Western blotting techniques, and PKCδ RNA levels were determined by Northern blotting, RT-PCR and Real-Time RT-PCR. Insulin stimulation increased PKCδ protein levels in whole cell lysates. This effect was not due to an inhibition by insulin of the rate of PKCδ protein degradation. Insulin also increased 35S-methionine incorporation into PKCδ within 5–15 min. Pretreatment of cells with transcription or translation inhibitors abrogated the insulin-induced increase in PKCδ protein levels. We also found that insulin rapidly increased the level of PKCδ RNA, an effect abolished by inhibitors of transcription. The insulin-induced increase in PKCδ expression was not reduced by inhibition of either PI3 Kinase or MAP kinase, indicating that these signaling mechanisms are not involved, consistent with insulin activation of PKCδ. Studies on cells transfected with the PKCδ promoter demonstrate that insulin activated the promoter within 5 min. This study indicates that the expression of PKCδ may be regulated in a rapid manner during the course of insulin action in skeletal muscle and raise the possibility that PKCδ may be an immediate early response gene activated by insulin.